أثر الألعاب الاجتماعية في تنمية التواصل الاجتماعي لدى أطفال الرياض (5-6) سنوات "دراسة تجريبية على رياض الأطفال في مدينة دمشق" - يوسف آصف; زيود لينا لطيف (Latakia University Journal - Arts and Humanities Sciences Series, 2013)
يعد اللعب أحد أهم الاحتياجات الحيوية للطفل الجديرة بالاهتمام والرعاية, وذلك لأن اللعب هو الخاصية والسمة الأساسية للطفولة, وهو المحرك والدافع المساعد في كل عمليات النضج والتكوين, يدرك فيه الطفل العالم بأسره, ووسيلته في اكتشاف ذاته وقدراته المتنامية, كما يعد من أنسب الطرق في التواصل والتفاعل الاجتماعي للطفل مع الآخرين. يعد التواصل الاجتماعي من العناوين الأساسية في منظومة الوجود الإنساني, فالإنسان يحتاج غريزياً للتواصل والتفاهم مع محاوريه تحقيقاً لمصالحه, وتأكيداً لطابعه الاجتماعي, إذ يمنحه التواصل الاجتماعي شعوراً بأنه جزءٌ ينتمي إلى المحيطين به, وأنه شخصٌ يشبه بقية الأشخاص, يتفاعل معهم, يؤثر ويتأثر بهم, كما يشبع رغباته ومطالبه وصولاً إلى تحقيق مزيد من الإنجازات. لذلك تركز الباحثة على بيان قدرة الألعاب الاجتماعية ودورها في إكساب الطفل المهارات اللازمة والمفاهيم الجديدة للتواصل مع الأطفال الآخرين بشكل سليم. لقد توصلت الباحثة إلى ضآلة قدرة الطريقة التقليدية المستخدمة عموماً في تعليم أطفال الرياض مقارنة بكفاءة وفعالية طريقة استخدام الألعاب الاجتماعية فيما يتعلق بإكساب وتعليم الطفل مهارات التواصل الاجتماعي. Playing is considered one of the most vital needs for the child which is worthy to attention and care. This is because playing is the basic idiosyncrasy and feature of childhood, and it is the motivation behind all processes of maturity and formation. Through playing, the child realizes the whole world, and it is his way to discover himself/herself and his/her abilities. Playing is considered the most suitable way for social communication and interaction with other children. Social communication is one of the basic features of human existence as the human being instinctively needs to communicate, come to an understanding with the others in order to achieve his / her goals, and emphasize his / her social nature. Social communication gives the child the feeling that he / she is part of the human environment. It gives the child the feeling of familiarity among other children. It helps the child to interact with others, fulfill his / her needs and achieve more of his / her goals. Therefore, the researcher focused on revealing the ability of social games and the role they play in giving the necessary skills and new conceptions that help the child to communicate with other children healthily. The researcher has found that the traditional teaching methods are less effective than the modern methods of using the social games to pass on to the child the knowledge and skills of the social communication.